Analisis Pemahaman Petani Kelapa Terhadap Zakat Pertanian di Desa Tegal Rejo Kabupaten Indragiri Hilir - Hidayatullah, Ifan Syafrudin; Astuti, Daharmi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
The background of this research is the lack of public knowledge and understanding of zakat and the lack of existence of zakat management organizations in emphasizing the importance of agricultural zakat so that people who have the potential to pay zakat are not by the provisions of zakat where zakat is something that must be issued if it has reached the nisab and levels and implemented when the nisab and haul have arrived. The research objective is how the level of public understanding of agricultural zakat, especially hybrid coconut farmers. The formulation of the research problem is what is the level of public understanding of zakat on coconut farming. The subjects of this study were the people of Tegal Rejo Village, Pelangiran District, Indragiri Hilir Regency, while the object in this study was the community's understanding of agricultural zakat. The type of research used is the type of field research. The data sources used are primary and secondary data. While the data collection techniques are questionnaires, observation, questionnaires, and documentation. To analyze the data using descriptive qualitative methods. The number of populations in this study was 85 people. Based on the results of the study, it can be concluded that through the respondents' answers, it can be concluded that the analysis of people's understanding of agricultural zakat Tegal Rejo, Kec. Pelangiran Kab. Inhil answered "good" about zakat on agriculture with a percentage of 64.70%.